EFFECT OF TOPICAL HUMIC ACID ON EXCISIONAL PALATAL WOUND HEALING: A HISTOPATHOLOGICAL AND HISTOMORPHOMETRIC STUDY IN RATS - Yusuf Ziya Dönmez; Aysun Akpınar; Fahrettin Göze (Cumhuriyet University, 2022)
Background: The purpose of the present study was to examine the effects of topical humic acid application on healing in oral mucosa wound in rats. Material and Methods A total of 12-week-old 72 Wistar male rats weighing 280-300 gr were used in the study. The rats were randomly grouped in 4 groups as the Control Group (K) to which no applications were made, Chlorhexidine (0.12%) Group (CHX), 80 mg/kg Humic Acid Group (HA80), and 150 mg/kg Humic Acid Group (HA150). Mucosal defects of 5-mm-diameter were induced with punch in the palatal areas of the rats. These groups were further divided into 3 sub-groups to be sacrificed on days 7, 14 and 21. Epithelization, ülceration, polymorphic nuclear leukocytes (PNL), mononuclear cells (MNL), fibroblast and vascularization were examined in histopathologic evaluations. In addition, photos of the tissue samples were taken and transferred to the computer medium for histo-morphometric examinations. Results As a result of the statistical analyses, no significant differences were detected among the groups in terms of epithelization degree, PNL and MNL cell infiltration on days 7, 14 and 21. The ulcerated areas were low in HA150 Group compared to the other groups, and there was a significant difference in this respect (p<0.05). Vascularization degrees were evaluated, the K Group and HA150 Group showed better results on day 7 (p<0.05). On days 14 and 21, no significant differences were detected among the groups (p>0.05). Wound area measurement scores were lower in HA150 Group compared to the other groups, and this result showed that the healing in HA150 Group was better (p<0.05). Conclusions As a result of the present study, it was found that humic acid increased wound healing in oral cavity.